THE EFFECT OF ORGANIZATIONAL JUSTICE, ORGANIZATIONAL CULTURE, AND CAREER DEVELOPMENT ON JOB SATISFACTION AT UPTD PUSKESMAS DEWANTARA, NORTH ACEH DISTRICT - Reyna Arsy Zulfa; Ibrahim Qamarius; A Hadi Arifin; Sullaida (RADJA PUBLIKA, 2025)
Job satisfaction at the Dewantara Health Center UPTD, North Aceh Regency is the focus of this study, which seeks to understand the role of organizational justice, culture, and career development in this context. Improving employee happiness requires research on how to create a more equitable workplace, strengthen corporate culture, and facilitate career advancement. Quantitative techniques were used in this study through a survey. All staff members of the Dewantara Health Center UPTD were the population, and 69 people were randomly selected to participate in the survey. Multiple linear regression was used to examine the data received from the structured questionnaire. There was a statistically substantial relationship between job satisfaction and organizational justice, organizational culture, and career growth. Individually, each of these factors also had a significant and beneficial impact. The three independent factors explained 64.6% of the variation in job satisfaction, according to the coefficient of determination (R²). To improve organizational productivity and employee well-being, these results emphasize the importance of implementing a fair, culturally supportive, and future-oriented human resource strategy.